The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/bies.202000240
|View full text |Cite
|
Sign up to set email alerts
|

The genetic structure of SARS‐CoV‐2 does not rule out a laboratory origin

Abstract: Severe acute respiratory syndrome‐coronavirus (SARS‐CoV)‐2′s origin is still controversial. Genomic analyses show SARS‐CoV‐2 likely to be chimeric, most of its sequence closest to bat CoV RaTG13, whereas its receptor binding domain (RBD) is almost identical to that of a pangolin CoV. Chimeric viruses can arise via natural recombination or human intervention. The furin cleavage site in the spike protein of SARS‐CoV‐2 confers to the virus the ability to cross species and tissue barriers, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 78 publications
2
53
0
1
Order By: Relevance
“…However, bioinformatic analyses revealed biases in codon usages that might reflect some genetic manipulation (Gu et al 2020). Segreto and Deigin develop the hypothesis of a genome modified by molecular engineering (Segreto and Deigin 2020). More thorough analyses are warranted to clarify this issue.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…However, bioinformatic analyses revealed biases in codon usages that might reflect some genetic manipulation (Gu et al 2020). Segreto and Deigin develop the hypothesis of a genome modified by molecular engineering (Segreto and Deigin 2020). More thorough analyses are warranted to clarify this issue.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Zhou et al 2020a;Lam et al 2020;Xiao et al 2020;Andersen et al 2020). However, in the absence of evidence regarding the last animal intermediate before human contamination (the "proximal" origin of the virus), some authors suggested that SARS-CoV-2 may have been manufactured in a laboratory (synthetic origin) (Segreto et Deigin 2020) .…”
Section: /26mentioning
confidence: 99%
“…However, bioinformatic analyses revealed biases in codon usages that might reflect some genetic manipulation(Gu et al 2020). Segreto and Deigin develop the hypothesis of a genome modified by molecular engineering(Segreto et Deigin 2020). More thorough analyses are warranted to clarify this issue.15/26Beyond the frame of existing national regulations (e.g.…”
mentioning
confidence: 99%
“…Additionally, there could be sequencing errors due to several factors such as poor sample quality, improper handling, secondary PCR enrichment, and low-quality measurements [16,18]. The RaTG13 strain was isolated in 2013, but its complete genomic sequence (GenBank ID MN996532) was submitted after the emergence of SARS-CoV-2 in 2020 [19]. Additionally, the RNA-dependent RNA polymerase (RdRp) gene of RaTG13 is identical to that of another bat CoV sequence BtCoV/4991 (GenBank ID KP876546) submitted in 2015 [19].…”
mentioning
confidence: 99%
“…The RaTG13 strain was isolated in 2013, but its complete genomic sequence (GenBank ID MN996532) was submitted after the emergence of SARS-CoV-2 in 2020 [19]. Additionally, the RNA-dependent RNA polymerase (RdRp) gene of RaTG13 is identical to that of another bat CoV sequence BtCoV/4991 (GenBank ID KP876546) submitted in 2015 [19]. Strikingly, NCBI KRONA analysis of the RaTG13 sequence suggested the possibility of DNA contamination, and the sequence was considered a fossil record [7,20].…”
mentioning
confidence: 99%